Sulfatase 1 and sulfatase 2 as novel regulators of macrophage antigen presentation and phagocytosis - Hyun-Je Kim; Hee-Sun Kim; Young-Hoon Hong (Yeungnam University Journal of Medicine, 2021)
Background Sulfation of heparan sulfate proteoglycans (HSPGs) is critical for the binding and signaling of ligands that mediate inflammation. Extracellular 6-O-endosulfatases regulate posttranslational sulfation levels and patterns of HSPGs. In this study, extracellular 6-O-endosulfatases, sulfatase (Sulf)-1 and Sulf-2, were evaluated for their expression and function in inflammatory cells and tissues. Methods Harvested human peripheral blood mononuclear cells were treated with phytohemagglutinin and lipopolysaccharide, and murine peritoneal macrophages were stimulated with interleukin (IL)-1β for the evaluation of Sulf-1 and Sulf-2 expression. Sulf expression in inflammatory cells was examined in the human rheumatoid arthritis (RA) synovium by immunofluorescence staining. The antigen presentation and phagocytic activities of macrophages were compared according to the expression state of Sulfs. Sulfs-knockdown macrophages and Sulfs-overexpressing macrophages were generated using small interfering RNAs and pcDNA3.1 plasmids for Sulf-1 and Sulf-2, respectively. Results Lymphocytes and monocytes showed weak Sulf expression, which remained unaffected by IL-1β. However, peritoneal macrophages showed increased expression of Sulfs upon stimulation with IL-1β. In human RA synovium, two-colored double immunofluorescent staining of Sulfs and CD68 revealed active upregulation of Sulfs in macrophages of inflamed tissues, but not in lymphocytes of lymphoid follicles. Macrophages are professional antigen-presenting cells. The antigen presentation and phagocytic activities of macrophages were dependent on the level of Sulf expression, suppressed in Sulfs-knockdown macrophages, and enhanced in Sulfs-overexpressing macrophages. Conclusion The results demonstrate that upregulation of Sulfs in macrophages occurs in response to inflammation, and Sulfs actively regulate the antigen presentation and phagocytic activities of macrophages as novel immune regulators.